Tingkat Keuntungan Bank di Indonesia setelah Krisis Subprime 2008 di Amerika Serikat - Pandu Adi Cakranegara (FIRM Journal of Management Studies, 2018)
Subprime Mortgage in America has a wide impact on the world including Indonesia. The researcher examines its relationship with banks in Indonesia. The economic downturn in the United States will have an impact on the global economic downturn. Thus, the Indonesian economy will also be affected. If there is an economic downturn, the financial sector in this case is represented by the banking sector, which will first decrease its value. The analysis used uses the method of analyzing financial statements. Based on the data from the Audited Financial Report, the banking sector growth and operational performance can be analyzed. The results found were the linkage of Du Pont's Stock Returns and ROE. High ROE will result in rising stock prices on the market. Nevertheless, market appreciation for each bank is not the same because there are banks that are more appreciated by the market or conversely there are banks that are not appreciated as high as other banks.